2018
DOI: 10.1039/c7tc03682e
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman scattering of alkyne-conjugated MoS2: a comparative study between metallic and semiconductor phases

Abstract: Raman enhancement on nonmetallic flat two-dimensional (2D) nanomaterial surfaces has attracted a great deal of attention since the discovery of graphene-enhanced Raman scattering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 35 publications
0
18
2
Order By: Relevance
“…With plasma treated MoS 2 , Sun et al 100 demonstrated the correlation between the amount of structural disorder and the formation of local dipoles which enhanced the overall SERS. Anbazhagan et al 101 proposed that in lithium-exfoliated MoS 2 , surface S and Mo vacancies are created that can promote dipole–dipole interactions with R6G, resulting in better substrate–molecule CT ( Fig. 6c ).…”
Section: Influences Of Defect Engineering On Semiconductorsmentioning
confidence: 99%
“…With plasma treated MoS 2 , Sun et al 100 demonstrated the correlation between the amount of structural disorder and the formation of local dipoles which enhanced the overall SERS. Anbazhagan et al 101 proposed that in lithium-exfoliated MoS 2 , surface S and Mo vacancies are created that can promote dipole–dipole interactions with R6G, resulting in better substrate–molecule CT ( Fig. 6c ).…”
Section: Influences Of Defect Engineering On Semiconductorsmentioning
confidence: 99%
“…To compensate for the lack of band gap, researchers have focused their attention on the transition metal dichalcogenides (TMDs). Molybdenum disulfide (MoS 2 ) has similar physical properties to graphene, but it contains some advantages that graphene cannot match [6,7,8,9]. The monolayer MoS 2 is a “sandwich” structure, whereby the upper and lower layers are the hexagonal planes composed of sulfur atoms, and the middle is a layer of metal molybdenum atoms.…”
Section: Introductionmentioning
confidence: 99%
“…7c, the intensity of typical absorption bands, such as at 612, 774, 1511 and 1650 cm À1 , exhibited high uniformity, which revealed that the AgNWs@PDA@AgNPs nanocobs could provide excellent SERS reproducibility. 38,43 Moreover, the results in Fig. 7d displayed that the relative standard deviation (RSD) values of Raman vibration at 612, 774, 1511 and 1650 cm À1 were about 14.89%, 16.46%, 15.28% and 14.55% (#20%) respectively.…”
Section: Resultsmentioning
confidence: 94%
“…eld because of the interparticles electromagnetic coupling of the aggregated AgNPs, and offered a great Raman signal enhancements to achieve single-molecule level detection. 37,38 From the SERS spectra of R6G molecules on AgNWs, AgNWs@PDA, AgNWs@PDA@AgNPs and AgNPs in Fig. S3a, † the AgNPs substrate could produce excellent enhancement effect, and the R6G detection limit on the AgNPs SERS substrate was about 1 Â 10 À11 M (Fig.…”
Section: Resultsmentioning
confidence: 99%